Implementasi Model PBL Dan Pendekatan TPACK Media Interaktif Meningkatkan Kemampuan Berpikir Kritis Serta Hasil Belajar - Fahrina Hikmah; Radiansyah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in research is the low learning activity, critical thinking and learning outcomes. This study aims to describe the improvement in the quality of learning through teacher activity and to describe the increase in student activity and critical thinking skills as well as to analyze student learning outcomes. The research method used a quantitative and qualitative approach with the type of Classroom Action Research (CAR) which was held in 3 meetings. The research subjects were fourth grade students at SDN Pengambangan 3 Banjarmasin totaling 22 students consisting of 11 male students and 11 female students. The data taken is qualitative data obtained through observing teacher activities, student activities and critical thinking skills then quantitative data for student learning outcomes is obtained through group and individual written tests, the completeness criteria set is ≥70. The results showed that 95.45% of student learning outcomes were complete. Teacher activity scores 28 very good criteria, student activity 90.91% with very active criteria and critical thinking skills 90.91 with very skilled criteria. Based on the data findings and results of this study, it can be concluded that using the PBL Model Interactive Media TPACK Approach in class IV. The results of this research can increase teacher activity, student activity, critical thinking skills and learning outcomes.